Kajian Pragmatik terhadap Tindak Tutur Bahasa dalam Podcast H. Pod Channel: Studi Kasus Pasangan LGBT - Fitrah Aminah; Mafaza Aulyani Hadi; Syarafina Yusrina; Rulina Rulianty Sihombing; M. Oky Fardian Gafari (STIKes Ibnu Sina Ajibarang, 2025)
This study examines the dynamics of speech acts in the H. POD Channel podcast that presents LGBT couples as speakers. The background of the research is based on the role of pragmatics in understanding the meaning of speech and the function of podcasts as a dialogic medium for sensitive issues. The purpose of this study is to identify the types of speech acts that appear and analyze the language strategies of the LGBT community in identity negotiation. The method used is descriptive qualitative with a case study approach; primary data in the form of podcast episode transcripts are analyzed using Austin and Searle's speech act theory, as well as secondary data from pragmatics literature. The results of the study show that assertive speech acts are most dominant, followed by expressive, directive, and commissive, which reflect the conveyance of facts, expression of feelings, invitation, and commitment. Language use also displays identity negotiation and responses to heteronormative norms. This study concludes that the pragmatics approach is effective in revealing the dynamics of communication and identity construction in digital public spaces.